Mechanisms of pH change in wood ant (Formica polyctena) nests - Jílková, Veronika (Jihočeská univerzita, 2011)
The aim of this study was to reveal mechanisms of pH change in wood ant nests. Contents of basic cations and glucose brought in ant food, i.e., honeydew and prey, into the nests were measured. Manipulation experiment was carried out to test effects of glucose and Ca2+ cations brought by ants into the nest on increase in pH.
Mechanisms of pH change in wood ant (Formica polyctena) nests
Keywords: wood ant; pH; basic cations; glucose; litter